The association between the dietary inflammatory index and cardiorespiratory fitness in United States young adults: a cross-sectional study from the National Health and Nutrition Examination Study, 1999–2004 - Wu, Bo; Qiu, Lanlan; Lin, Yun; Lin, Qian; Pan, Yuxiong (Frontiers in Nutrition, 2024)
Abstract Background: Cardiorespiratory fitness (CRF) is a vital indicator of overall health and cardiovascular efficiency. Systemic inflammation significantly impacts CRF, and reducing systemic inflammation may serve as an effective strategy to improve CRF. Diet plays a crucial role in systemic inflammation, but daily dietary intake typically involves multiple elements rather than a single nutrient. The Dietary Inflammatory Index (DII) provides an overall assessment of dietary inflammation on the basis of the anti-inflammatory and pro-inflammatory effects of the nutrients consumed. However, the relationship between DII and CRF is not yet well understood. Aims: To examine the association between the DII and CRF. Method: This study analyzed 3,087 participants from the National Health and Nutrition Examination Survey (NHANES) between 1999 and 2002. The study subjects were divided into three distinct groups by DII tertile: T1 (n=1,027), T2 (n=1,029), and T3 (n=1,031). The associations between DII levels and CRF were examined via logistic regression analysis and restricted cubic splines (RCSs). Results: Elevated DII scores were significantly linked to low CRF levels. Compared with those in the lowest tertile, participants in the highest DII tertile exhibited a greater prevalence of low CRF (T1: 10.85%, T2: 16.32%, T3: 19.31%). In the model with full adjustments, elevated scores on the DII were consistently linked with a heightened likelihood of low CRF (OR: 1.17, 95% CI: 1.07–1.28; P<0.001). Compared with those in the T1 group, participants with higher DIIs had an increased risk of lower CRF (T2: OR: 1.42, 95% CI: 1.01-2.01, P=0.046; T3: OR: 1.71, 95% CI: 1.22-2.40, P=0.003). Additionally, a significant interaction (P = 0.045) between sex and the DII for low CRF was observed within the population. Conclusions: A higher DII score is linked to an elevated risk of low CRF. Moreover, sex can impact CRF, with women being more prone to low CRF.